What is the capacity of the children's nursing workforce in seven selected Sub-Saharan African countries? Gathering insights from Botswana, Kenya, Namibia, Malawi, South Africa, Uganda and Zambia - North, Natasha (Department of Paediatrics and Child Health, 2019)
Background This study attempted to identify as far as possible the extent of the children’s nursing workforce in five selected countries in the sub-Saharan African region. Strengthening children’s nursing training has been recommended as a primary strategy to reduce the underfive mortality rate in African nations, including South Africa and Malawi. The current level of data monitoring capacity worldwide means that it is not possible to disaggregate the children’s nursing workforce in countries in the World Health Organisation African Region from the data provided by the WHO Global Atlas of the Health Workforce database. Yet developing an accurate depiction of the specialist children’s nursing workforce is a necessary step towards optimizing children’s health service delivery. Methods In attempting to respond to this need, this study adheres to a collaborative research philosophy, using a convergent parallel mixed methods design, incorporating a scoping documentary review, together with quantitative (surveys and case study compilation) and qualitative (interview) components collected independently and then integrated during analysis and interpretation, to generate data addressing three related questions: how many children’s nurses are believed to be in practice nationally; how many such nurses are recorded on the nursing register nationally; and how many children’s nurses are being produced through training. Results Findings suggest there are approximately 3 728 children’s nurses across the five countries in this study. A combined total of 260 children’s nurses are produced through training each year across the five countries on average. Survey responses, interview data and content analysis of items identified through the scoping review suggest that adequate information regarding the children’s nursing workforce is not currently available to inform decision-making. Conclusion In conclusion, it is hoped that the data generated might contribute towards identifying the size of the children’s nursing workforce, as a first step towards identifying what would represent a viable and sustainable regional children’s nursing workforce for the future.